Wine growers’ propensity to adopt digital precision farming technologies: integrating risk attitudes to the Technology Acceptance Model - Adriano Biondo; Giuseppina Rizzo; Giuseppina Migliore; Antonino Galati (Research in Globalization)
The objective of this study is to explore the propensity of wine growers to implement precision agriculture technologies in their core business. The investigation will focus on the main cognitive, social and risk factors affecting this intention. The Technology Acceptance Model, TAM2, integrated with risk attitudes was adopted. Data were collected from 128 Sicilian wine producers using a questionnaire, following which the PLS-SEM was employed for analysis. The findings reveal that Perceived usefulness and Ease of use of innovative technologies are the most influential factors in the decision-making process. Nevertheless, farmers’ risk attitudes have been shown to significantly influence their decisions about adopting Precision Agriculture Technologies. Despite the potential benefits, farmers who are risk-averse demonstrate a greater reluctance. Additional barriers include high costs, lack of training and compatibility with traditional practices. This study enhances the existing literature by offering insights into the key factors influencing farmers’ intention to implement PATs. Moreover, the findings offer significant insights for wine businesses and policymakers, underscoring the efficacy of targeted training programmes, risk mitigation strategies, and financial incentives in expediting the digital transformation of the viticulture sector. More in detail, the results allow wineries to understand the main barriers to innovation in the management of their businesses. This understanding enables them to define targeted strategies. Secondly, the results can guide the definition of policy measures with the potential to effect meaningful change in the wine sector, with a view to economic and environmental sustainability. The study contributes to the sustainable future of the agricultural industry by reducing the digital divide, enhancing productivity and environmental efficiency, and improving market competitiveness.